2022
DOI: 10.3390/life12101602
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Phellandrene and Alpha-Phellandrene-Rich Essential Oils: A Systematic Review of Biological Activities, Pharmaceutical and Food Applications

Abstract: Alpha-phellandrene is a very common cyclic monoterpene found in several EOs, which shows extensive biological activities. Therefore, the main focus of the present systematic review was to provide a comprehensive and critical analysis of the state of the art regarding its biological activities and pharmaceutical and food applications. In addition, the study identified essential oils rich in alpha-phellandrene and summarized their main biological activities as a preliminary screening to encourage subsequent stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 127 publications
1
15
0
Order By: Relevance
“…The cyclic monoterpene α-phellandrene was introduced for public use in the 1940s [ 60 ]. It represents a colorless liquid, characterized by a peppery, woody, and herbaceous aroma [ 60 ]. It could be found in cosmetics, food, and EOs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cyclic monoterpene α-phellandrene was introduced for public use in the 1940s [ 60 ]. It represents a colorless liquid, characterized by a peppery, woody, and herbaceous aroma [ 60 ]. It could be found in cosmetics, food, and EOs.…”
Section: Resultsmentioning
confidence: 99%
“…It could be found in cosmetics, food, and EOs. Nowadays, α-phellandrene has been characterized by a broad spectrum of pharmacological activities, including antimicrobial, anti-inflammatory, antitumoral, analgesic, and insecticidal activities ( Figure 4 ) [ 60 , 61 , 62 , 63 ]. Alpha-phellandrene accelerated wound closure due to collagen deposition and demonstrated good wound-healing properties [ 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even now, dill water also known as “gripe water” is commonly used in folk remedies and Ayurvedic medicine to treat digestive and sleep problems, especially in children. Dill is prescribed to alleviate flatulence and promote expulsion of the placenta during delivery, and to stimulate milk flow in lactating mothers 1,4,5,11,14–18 . Currently, preclinical research has identified antioxidant, anti-inflammatory, analgesic, antimicrobial, neuroprotective, and anticancer properties of dill extracts, to name a few 5,6 .…”
mentioning
confidence: 99%
“…Dill is prescribed to alleviate flatulence and promote expulsion of the placenta during delivery, and to stimulate milk flow in lactating mothers. 1,4,5,11,[14][15][16][17][18] Currently, preclinical research has identified antioxidant, antiinflammatory, analgesic, antimicrobial, neuroprotective, and anticancer properties of dill extracts, to name a few. 5,6 Recent clinical trials investigated dill and its extracts for managing risk factors for diabetes and cardiovascular disease, as well as in improving outcomes during labor and delivery.…”
mentioning
confidence: 99%
“…1 • July/August 2023 promote expulsion of the placenta during delivery, and to stimulate milk flow in lactating mothers. 1,4,5,11,[14][15][16][17][18] Currently, preclinical research has identified antioxidant, antiinflammatory, analgesic, antimicrobial, neuroprotective, and anticancer properties of dill extracts, to name a few. 5,6 Recent clinical trials investigated dill and its extracts for managing risk factors for diabetes and cardiovascular disease, as well as in improving outcomes during labor and delivery.…”
mentioning
confidence: 99%